2017
DOI: 10.1103/physrevlett.119.084501
|View full text |Cite
|
Sign up to set email alerts
|

Motion of a Free-Settling Spherical Particle Driven by a Laser-Induced Bubble

Abstract: We document experimentally four different interactions of a laser-induced bubble and a free-settling particle, with different combinations of the geometric and physical parameters of the system. Our force balance model shows that four nondimensional factors involving the particle radius a, the maximum bubble radius R_{max}, the initial separation distance l_{0} between the particle center and the bubble center, the fluid viscosity μ_{f}, and the particle and fluid densities ρ_{p} and ρ_{f}, respectively, in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The fluid is water at 20 • C. As indicated, boundary conditions are set on the domain including a velocity inlet, a pressure outlet, a symmetry boundary at mid-span, a no-slip wall on foil surface, slip wall boundaries on upper wall, lower wall and side wall. The inlet velocity v in is 6.97 m/s, which means that the Reynolds number Re is 1.05×10 6 . The reference location for C p and C σ is the inlet boundary.…”
Section: Cfd Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid is water at 20 • C. As indicated, boundary conditions are set on the domain including a velocity inlet, a pressure outlet, a symmetry boundary at mid-span, a no-slip wall on foil surface, slip wall boundaries on upper wall, lower wall and side wall. The inlet velocity v in is 6.97 m/s, which means that the Reynolds number Re is 1.05×10 6 . The reference location for C p and C σ is the inlet boundary.…”
Section: Cfd Setupmentioning
confidence: 99%
“…Cavitation is a commonly seen phenomenon in hydrodynamic turbomachinery cases such as pumps and hydroturbines [1][2][3]. It usually has bad influences including noise [4], vibration [5] and material damage [6]. For this reason, cavitating flow in hydraulic turbomachinery has been widely studied by researchers to understand its mechanism, behavior and influence.…”
Section: Introductionmentioning
confidence: 99%
“…They also developed an analytical model for the particle behavior after the disappearance of the bubble showing that the particle velocity inversely depends on the density and size of the particle, and approximately on the fourth power of the initial distance from the bubble. Wu et al [29] reported an investigation to further understand the mechanism of motion of a free-settling spherical particle driven by a laser-induced bubble, with fewer restrictions and smaller disturbances to the motions of the particle and the cavitation bubble than in the studies above. The maximum radius of the cavitation bubble is about 2 mm while the size of particles (0.1-0.5 mm in radius) is much smaller than the bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic cavitation is defined as the formation and pulsation of gas cavities in a liquid under the action of an acoustic field [1,2]. The cavities often grow as microbubbles and exhibit a cache of exotic phenomena in their relatively short lifetime.…”
Section: Introductionmentioning
confidence: 99%